2013
DOI: 10.1016/j.marpolbul.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Drawing lines at the sand: Evidence for functional vs. visual reef boundaries in temperate Marine Protected Areas

Abstract: Marine Protected Areas (MPAs) can either protect all seabed habitats within them or discrete features. If discrete features within the MPA are to be protected humans have to know where the boundaries are. In Lyme Bay, SW England a MPA excluded towed demersal fishing gear from 206 km(2) to protect rocky reef habitats and the associated species. The site comprised a mosaic of sedimentary and reef habitats and so 'non reef' habitat also benefited from the MPA. Following 3 years protection, video data showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 67 publications
0
55
1
Order By: Relevance
“…In this study, we found that despite increases in the average abundance of Ross coral across each fishing treatment since the Lyme Bay SAC was implemented, no significant effect of time on abundance was found. This differs to the findings of the short‐term studies, that were conducted 3 years following the establishment of the MPA (Sheehan, Cousens, et al., ; Sheehan, Stevens, et al., ), which observed significant increases in abundance over time. Hinz et al.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In this study, we found that despite increases in the average abundance of Ross coral across each fishing treatment since the Lyme Bay SAC was implemented, no significant effect of time on abundance was found. This differs to the findings of the short‐term studies, that were conducted 3 years following the establishment of the MPA (Sheehan, Cousens, et al., ; Sheehan, Stevens, et al., ), which observed significant increases in abundance over time. Hinz et al.…”
Section: Discussioncontrasting
confidence: 99%
“…Sheehan, Cousens, et al. () and Sheehan, Stevens, et al. () reported much higher abundances of king scallops in the areas of seabed they studied within Lyme Bay, which could suggest that the areas (type) of seabed surveyed in this study may have been less suitable for king scallops, or these differences may relate to temporal and spatial variation in recruitment.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…While frame grabs were only analysed if they were on ‘reef’ habitat (which constituted seabed with rock, boulders and cobbles), reef associated fauna, such as soft corals Alcyonium digitatum (Linnaeus, 1758) and upright bryozoans Pentapora fascialis , were also observed on sediments that appeared to overlay bedrock [41].…”
Section: Resultsmentioning
confidence: 99%